Irradiation of regional lymph node areas in breast cancer – Dose evaluation according to the Z0011, AMAROS, EORTC 10981-22023 and MA-20 field design. (January 2020) - Borm, Kai Joachim; Oechsner, Markus; Düsberg, Mathias; Buschner, Gabriel; Weber, Wolfgang; Combs, Stephanie Elisabeth; Duma, Marciana-Nona
Highlights: The actual dose distribution resulting from field design of randomized trials addressing lymph node irradiation is mostly unknown. For this study, treatment plans were designed according to the study protocols of 4 randomized trials. Dose evaluation in areas at risk revealed relevant differences from the prescribed dose. Abstract: Objective: The purpose of this study was to estimate the dose distribution from randomized trials (MA.20, EORTC 22922-10925 (EORTC), AMAROS and the Z0011 trial) on lymph node (LN) irradiation on a large LN atlas. Methods: 580 F 18 -FDG-PET/CT positive LN metastases of 235 patients were transferred rigidly and non-rigidly to three "template CTs" (standard, obese and slender patient). Further, the LN clinical target volumes (CTVs) were contoured according to the ESTRO-guidelines. Treatment plans were designed (each for the left and right side) for all patients based on the study protocols of the MA.20, EORTC, AMAROS and Z0011 trial. Subsequently, the dose distribution in the ESTRO-CTVs and in the 580 LNs were assessed. Results: Our results reveal variable dose coverage (26.8 ± 17.3 Gy–53.0 ± 1.8 Gy) in the targeted LN areas (ESTRO-CTV and LN) in dependence of the treatment planning design and the patients' body shape. None of the treatment plan designs provided full dose coverage to the lymphatic drainage system. High tangent irradiation resulted in a similar dose distribution in L I and II compared to the AMAROS field design. Conclusion: Inclusion of the entire lymphatic system may not be necessary for all patients to reproduce the oncologic benefit shown in the randomized LN-irradiation trials. Inclusion of axillary level II and extension of the supraclavicular CTV can be considered in selected high-risk patients, based on dose recalculation of the MA.20 trial. Further, our results amplify earlier assumptions that irradiation may have accounted for the good results after SLND alone in the Z0011 trial.